Tracing U mobility in deep groundwater using Ra isotopes - Krall, L; Auqué, L; Tullborg, E; Suksi, J; Trezzi, G; Garcia-Orellana, J; Andersson, P; Porcelli, D (Elsevier, 2017)
The mobility of natural U is compared among four boreholes in a fractured granite using Ra isotopes and geochemical modelling. 222Rn/226Ra activity ratios (ARs) spanning an order of magnitude underline differences in reactive surface area. (224Ra/228Ra)ARs up to 9 indicate recent changes in hydrogeochemistry, and (226Ra/228Ra)ARs 0.6-30 indicate variable deposition of U. Dissolved U is related to dissolution of a solid U(VI) phase by groundwater with HCO3− >20 mg·L-1. U reduction is hindered by Ca2UO2(CO3)30.